"SIMBurns": A high-fidelity simulation program in emergency burn management developed through international collaboration. Issue 1 (February 2019) - D'Asta, Federica; Homsi, Joseph; Sforzi, Idanna; Wilson, David; de Luca, Marco
Highlights: Emergency burn care requires both medical knowledge and non-technical skills. Non-technical skills include communication, leadership and coordinated teamwork. SIMBurns is a novel full-day course developed through international collaboration. This high-fidelity simulation program effectively teaches non-technical skills. Through SIMBurns, human errors can be prevented, and patient safety can be improved. Abstract: Acute management of a severely burned patient is an infrequent and stressful situation that requires medical knowledge as well as immediate coordinated action. Many adverse events in health care result from issues related to the application of 'non-technical' skills such as communication, teamwork, leadership and decision making rather than lack of medical knowledge. Training in these skills is known as Crisis Resource Management (CRM) training. In order to create well-prepared burn teams, it is critical to teach CRM principles through high-fidelity simulation (HFS). While CRM teaches foundational non-technical skills, HFS incorporates lifelike, whole-body, fully-responsive mannequins in order to provide a realistic emergency situation. The aim of the study is to describe the development of a novel high-fidelity simulation course called "SIMBurns: High Fidelity Simulation Program for Emergency Burn Management" that uses CRM as its foundation and is focused on management of burn injuries. The course was designed by a panel of simulation and burns experts from Meyer Children's Hospital in Italy and Birmingham Children's Hospital in the U.K. Simulation Program experts were certified by Boston Children's Hospital's Simulation Program. In this paper, we describe the course's design, development, structure, and participant's assessment of the course. Since the creation of the SIMBurns course in 2013, 9 courses have been conducted and 101 participants have attended the course. The course was well-received and its "Overall Satisfaction" was rated at 4.8/5. The primary objective in the SIMBurns course – to teach teamwork and CRM skills to medical staff involved in emergency burn care – was also met at 4.8/5. Participants felt that the course developed their ability to interact with other team members, further improved their understanding of how to appropriately use resources, emphasized the importance of role clarity and developed their communication skills. Additional quantitative and qualitative analyses obtained from participants were also reviewed after each course. The SIMBurns course aims to contribute to the education of those in healthcare in order to improve patient safety and to continue advancing the education of our emergency burn care teams.